1997
DOI: 10.1364/ao.36.005647
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations and laser Doppler flow measurements with high penetration depth in biological tissuelike head phantoms

Abstract: Laser Doppler flow measurements on biological tissuelike phantoms have shown that penetration depths of 30 mm could be obtained, thus exceeding the penetration depth of commercial instruments for the measurement of skin perfusion by more than an order of magnitude. Monte Carlo simulations were performed and compared with measurement results obtained on a headlike tissue model to quantify the influence of perfusion of the scalp on the cortex perfusion results. We found Doppler frequency spectra to be independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…a high degree of multiple Doppler shifts, where the Doppler spectrum only depend on µ s and not the anisotropy. 8,28 Binzoni et al 9 have suggested an alternative approach that takes multiple Doppler shifts into account. Their approach, based on a theoretical framework by Bonner et al, 3 assumes a Gaussian RBC velocity distribution in the tissue and that the RBC phase function is described by the Rayleigh-Gans approximation.…”
Section: Discussionmentioning
confidence: 99%
“…a high degree of multiple Doppler shifts, where the Doppler spectrum only depend on µ s and not the anisotropy. 8,28 Binzoni et al 9 have suggested an alternative approach that takes multiple Doppler shifts into account. Their approach, based on a theoretical framework by Bonner et al, 3 assumes a Gaussian RBC velocity distribution in the tissue and that the RBC phase function is described by the Rayleigh-Gans approximation.…”
Section: Discussionmentioning
confidence: 99%
“…The photon packet steps were generated by means of the variable step size method (Prahl et al 1989). The model describing the change of the photon packet direction after each collision was represented by the Henyey-Greenstein probability density function (Henyey and Greenstein 1941) independently of the fact that the scatterer was a moving particle or not (Soelkner et al 1997, Kienle 2001. Reflection of the photon packets on the boundaries was treated as an all-or-none problem by using the probability density functions derived from the Snell-Descartes law and Fresnel's formulae.…”
Section: Monte Carlo Methods and Generation Of The Power Spectrummentioning
confidence: 99%
“…The laser-Doppler shift for each individual photon (packet) was computed by means of the method published in Soelkner et al (1997) (see equation (1)). After each scattering event it was decided if the scatterer was a moving particle by sampling a uniform random number ξ ∈ [0, 1] and by defining the probability of having a moving particle P move ∈ [0, 1].…”
Section: Monte Carlo Methods and Generation Of The Power Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method implies only a slight modification of the 'classical' MC approach as it exists for direct generation of P i (ω) (see e.g. Soelkner et al (1997)). …”
Section: Introductionmentioning
confidence: 99%